Byssal attachment etchings: a new bioerosion trace on recent oysters - Romero, María Virginia (2013)
Byssate bivalves can be attached to hard substrates by byssal threads. Dissolution of the substrate to which they are attached may leave superficial bioerosion traces. This study reports the scars produced by byssus of Mytilus edulis and Aulacomya atra recorded in shells of Ostrea puelchana. Oyster valves were cut and gold-sputtered prior to scanning electron microscope observation. Each byssal thread leaves a characteristic scar on shells substrate. They etch an irregular trace on the substrate which may reach a diameter of several centimeters. These etching-traces comprise shallow round/oval holes of variable number and placement. A bundle of pits corresponding to fibers that compose the thread core was identified in the interior of each hole.We suggest that this trace could be included in the ethological class Fixichnia. The description of this trace would allow adjusting the composition of fossil assemblages and therefore paleoenvironmental interpretations in those cases in which mytilid shells have not been preserved. The recognition of this trace along with other ones of tracemakers with reotaxis or positive phototaxis could be useful in inferring the life habit of fossil biogenic substrates and in reconstructing their taphonomic history.